Metal(loid) Analysis of commercial rice from Malaysia using ICP‑MS: Potential health risk evaluation - Navaretnam, Raneesha; Hassan, Hadirah Nasuha; Mohd Isa, Noorain; Aris, Ahmad Zaharin; Ley, Juen Looi (Springer Science and Business Media LLC, 2023)
Rice is a predominant staple food in many countries. It is a great source of energy but can also accumulate toxic and trace metal(loid)s from the environment and pose serious health hazards to consumers if overdosed. This study aims to determine the concentration of toxic metal(loid)s [arsenic (As), cadmium (Cd), nickel (Ni)] and essential metal(loid)s [iron (Fe), selenium (Se), copper (Cu), chromium (Cr), cobalt (Co)] in various types of commercially available rice (basmati, glutinous, brown, local whites, and fragrant rice) in Malaysia, and to assess the potential human health risk. Rice samples were digested following the USEPA 3050B acid digestion method and the concentrations of metal(loid)s were analyzed using an inductively coupled plasma mass spectrometry (ICP-MS). Mean concentrations (mg/kg as dry weight) of metal(loid)s (n=45) across all rice types were found in the order of Fe (41.37)>Cu (6.51)>Cr (1.91)>Ni (0.38)>As (0.35)>Se (0.07)>Cd (0.03)>Co (0.02). Thirty-three percent and none of the rice samples surpassed, respectively, the FAO/WHO recommended limits of As and Cd. This study revealed that rice could be a primary exposure pathway to toxic metal(loid)s, leading to either noncarcinogenic or carcinogenic health problems. The non-carcinogenic health risk was mainly associated with As which contributed 63% to the hazard index followed by Cr (34%), Cd (2%), and Ni (1%). The carcinogenic risk to adults was high (>10-4) for As, Cr, Cd, and Ni. The cancer risk (CR) for each element was 5 to 8 times higher than the upper limit of cancer risk for an environmental carcinogen (<10-4). The findings from this study could provide the metal(loid)s pollution status of various types of rice which are beneficial to relevant authorities in addressing food safety and security-related issues.